(untitled) (Journal of Tikapur Multiple Campus, 2015)
Strategy Management is the ideology of effective process of creating, transforming and using resourse more effectively. This report indicates to achieve better results through effective management of human resourse strategy in organization. As a result, Nepalese Manufacturing Industries are more innovative and achieve better performance if they consider Strategic Management. Strategic Management suggests for diagnosis the change, introduce change and evaluate change in change process. However, small statistics, small coverage area of manufacturing concern, and opinion of officer level staffs, area of strategic only price and advertisement are the main limitation of this report.